Risk assessment of the Xigou debris flow in the Three Gorges Reservoir Area - Zhang, Anle; Dai, Zhenwei; Qin, Weibing; Fu, Xiaolin; Gao, Jingxuan; Guo, Lianjun; Liu, Liang; Jiang, Xiannian; Wang, Heng (Frontiers in Ecology and Evolution, 2023)
On June 18, 2018, under the influence of heavy rainfall, a debris flow disaster broke out in Xigou village of the Three Gorges Reservoir Area in Chongqing, causing some residential houses to be buried along with great economic losses. The on-site investigation found many loose solid material sources in the debris flow gully. Under the conditions of heavy rainfall, debris flows are prone to occur again, which would seriously threaten the lives and property of nearby residents. In this paper, taking the Xigou debris flow as a research case, numerical simulation by rapid mass movements simulation (RAMMS) is used to invert the movement process of the 2018 debris flow event; the dynamic calculation parameters of the Xigou debris flow event are obtained; a quantitative hazard prediction of debris flows with different recurrence intervals (30, 50, and 100 years) is carried out in the study area; and risk assessment is conducted based on the vulnerability characteristics of the disaster-bearing bodies in the study area. The results show that the maximum accumulation thickness of debris flow in the 30-year, 50year, and 100-year recurrence intervals is 6.54 m, 10.18 m, and 10.00 m, respectively, and the debris flow in the 100-year recurrence interval has the widest influence range and greatest hazard. The low-, medium-, and high-risk areas account for 75%, 23%, and 2%, respectively. The high-risk area mainly includes some buildings near the #1 and #2 gullies. This study provides support for the prevention and control of potential debris flow disasters in Xigou village and a scientific basis for disaster prevention and mitigation in the Three Gorges Reservoir area.